Fluorescent properties of the kindling fluorescent protein (KFP) at acidic pH values - Goryashchenko, A.S.; Rusanov, A.L.; Mironov, V.A.; Nemukhin, A.V.; Savitsky, A.P. (ALT Proceedings, 2026)
Kindling fluorescent protein (KFP) is the photoswitchable protein which can be used in high-resolution microscopy and as a quencher in FRET-sensors. Fluorescent properties of KFP depend on pH value. In this paper we investigate the influence of pH on the spectral properties and kindling/quenching ability of KFP in the acidic pH region. Shift to the acidic region leads to the increase of fluorescence intensity of KFP over time. The excitation spectrum has a new peak near 455nm, giving two peaks - 530 and 590nm – in emission spectrum. We can assume that this maximum corresponds to the appearance of protonated form of the KFP chromophore. Analysis of fluorescence decay curves of KFP in H2O and D2O showed the presence of the kinetic isotope effect, which can be caused by the proton transfer from solvent molecules to the KFP chromophore, confirming the hypothesis that in the acidic pH region protonated form of KFP chromophore appears. At acidic pH irradiation of KFP with green light doesn’t lead to fluorescence increase, while blue light doesn’t quench the fluorescence. It means that KFP is also in the bright form, and there is no conformational states of protein which can be quenched by blue light.